Uptake of carbamazepine by rhizomes and endophytic bacteria of Phragmites australis - Sauvêtre, Andrés; Schröder, Peter (Frontiers in Plant Science, 2015)
Carbamazepine is an antiepileptic and mood-stabilizing drug which is used widely in Europe and North America. In the environment, it is found as a persistent and recalcitrant contaminant, being one of the most prominent hazardous pharmaceuticals and personal care products in eﬄuents of wastewater treatment plants. Phragmites australis is one of the species with both, the highest potential of detoxification and phytoremediation. It has been used successfully in the treatment of industrial and municipal wastewater. Recently, the identification of endophytic microorganisms from different plant species growing in contaminated sites has provided a list of candidates which could be used as bio-inoculants for bioremediation of difficult compounds. In this study, Phragmites australis plants were exposed to 5 mg/L of carbamazepine. After 9 days the plants had removed 90% of the initial concentration. Endophytic bacteria were isolated from these plants and further characterized. Phylogenetic analysis based on 16S rDNA sequencing revealed that the majority of these isolates belong to three groups: Proteobacteria, Actinobacteria, and Bacteroidetes. Carbamazepine uptake and plant growth promoting (PGP) traits were analyzed among the isolates. Ninety percent of the isolates produce indole acetic acid (IAA) and all of them possess at least one of the PGP traits tested. One isolate identified as Chryseobacterium taeanense combines good carbamazepine uptake and all of the PGP traits. Rhizobium daejeonense can remove carbamazepine and produces 23 μg/mL of IAA. Diaphorobacter nitroreducens and Achromobacter mucicolens are suitable for carbamazepine removal while both, Pseudomonas veronii and Pseudomonas lini show high siderophore production and phosphate solubilization. Alone or in combination, these isolates might be applied as inoculates in constructed wetlands in order to enhance the phytoremediation of carbamazepine during wastewater treatment.